Application of environment learning models to the results of motive design in decorative design courses - Yusmerita Yusmerita; Yulia Aryati; Puji Hujria Suci (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study intends to increase the creative results of student motif designs in the Decorative Design course by applying a learning model based on the natural environment (Environment Learning). This type of research is classroom action research (CAR) with a qualitative approach. The subjects in this study were D3 students of the Fashion Design Study Program, totaling 37 people. Data collection techniques used student observation sheets, student activity sheets, student design results tests and questionnaires via Google form. The results of this study are learning decorative design in Cycle II it is known that as many as 32 students who have completed the competency in designing decorative motifs after applying the environmental learning learning model with an acquisition score of 86.48%, while students who did not complete as many as 5 students with acquisitions percentage value of 13.51%. So it was concluded that the percentage increase from cycle I to cycle II was 18.91%.